2021
DOI: 10.1063/5.0041500
|View full text |Cite
|
Sign up to set email alerts
|

Low-force elastocaloric refrigeration via bending

Abstract: Elastocaloric cooling has been identified as a promising alternative to high global warming potential vapor compression cooling. Two key bottlenecks to adoption are the need for bulky/expensive actuators to provide sufficient uniaxial stress and inadequate elastocaloric material fatigue life. This paper defines the physics that govern performance of axisymmetric flexural bending for use as an emerging low-force and low-fatigue elastocaloric heating and cooling mechanism and further demonstrates a continuous ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…This deepened the theory of the effect of strain rate on mechanical behavior. 7,9,13,16 Furthermore, the inuence of the phase content evolution processes on the mechanical behavior at different strain rates was analyzed. From the above analysis of the effect of strain rate on the phase content evolution processes and the mechanical behavior, it can be seen that point A was the end point at which the stress and strain maintained a linear relationship and the point at which the BCC content started to decrease from 100% as well.…”
Section: 32mentioning
confidence: 99%
See 1 more Smart Citation
“…This deepened the theory of the effect of strain rate on mechanical behavior. 7,9,13,16 Furthermore, the inuence of the phase content evolution processes on the mechanical behavior at different strain rates was analyzed. From the above analysis of the effect of strain rate on the phase content evolution processes and the mechanical behavior, it can be seen that point A was the end point at which the stress and strain maintained a linear relationship and the point at which the BCC content started to decrease from 100% as well.…”
Section: 32mentioning
confidence: 99%
“…And the results also showed that the DT adi increased gradually with increasing strain rates due to an increasing fraction of materials subjected to stress-induced martensite and a better adiabatic state. 10 The experimental method has been widely adopted and achieved many achievements in the study of the inuence of strain rate on the elastocaloric effect of Ni-Ti-based, [11][12][13] Cubased, 14 Fe-based 15 and Ni-Mn-based alloys. 16 However, limited by the experimental method, the essence of the effect of strain rate on mechanical behavior remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the above-mentioned devices are all targeted on miniature scale, they are just proof-of-concepts and all of them are based on SSHT mechanism [38]. The gap in the EC research field that this project wants to fill is the development of a small-scale device not based on SSHT anymore, but realized through the concept of AeR (where air is the heat transfer fluid) and, at the same time specifically targeted on the cooling of electronic devices in terms of power demand, temperature range and size.…”
Section: State Of the Art Of The Elastoclaoric Technologymentioning
confidence: 99%
“…The substantial difference lies in the method of load application: tensile and bending. The prototype based on bending [38] consists of two mini channels (an upper and a downer one) where wires of elastocaloric materials are located along the direction of the HTF since they are anchored to the ends through bars. A long bar system separates the two channels.…”
Section: The Check Temperature Prototypementioning
confidence: 99%
“…[21,22] Therefore, developing new type of polymeric solid-state cooling strategies and materials is a hot topic and still a challenge. Examples include cooling strategies such as cooling by twisting (twistocalirc) [12] and bending, [23] and new type of cooling materials such as polyethylene and nylon, [12] poly(vinylidene fluoride) (PVDF), [24][25][26] and liquid crystalline elastomers. [27,28] Poly-p-phenylene benzobisoxazole (PBO) is one of the strongest fiber materials with ultra-high modulus and excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%